RELATIONSHIP OF HBA1C WITH SERUM TOTAL CHOLESTEROL AND TRIGLYCERIDE IN DIABETIC PATIENTS (The Research of Medical Science Review, 2025)
Background: Type 2 diabetes mellitus (T2DM) is frequently accompanied by dyslipidemia, contributing to cardiovascular risk. Glycated hemoglobin (HbA1c) reflects long-term glycemic control and may be associated with lipid abnormalities. Objective: To determine correlation of HbA1c with serum total cholesterol and triglyceride in diabetic patients. Methods: A cross-sectional study was conducted on 217 patients with T2DM. HbA1c, serum cholesterol, and triglycerides were measured. Correlation was assessed using Spearman’s correlation coefficient. Stratified analyses were performed to determine variations by demographic and clinical factors. Results: Mean HbA1c was 9.20% ± 2.43. Significant positive correlations were observed between HbA1c and triglycerides (r = 0.271, p < 0.05), and between HbA1c and cholesterol (r = 0.212, p < 0.05). Post-stratification, stronger correlations were noted in females (HbA1c–triglycerides: r = 0.3074, p = 0.0003) and non-hypertensive individuals (r = 0.3881, p < 0.0001). Smokers showed the highest correlation between HbA1c and triglycerides (r = 0.4876, p = 0.0051). Conclusion: HbA1c shows a statistically significant correlation with lipid parameters in T2DM patients, with notable variation across subgroups. These findings highlight the importance of individualized risk assessment in diabetic care.